Genome−wide identification and analysis of LEA_2 gene family in alfalfa (Medicago sativa L.) under aluminum stress - Zhang, Yujing; Fan, Nana; Wen, Wuwu; Liu, Siyan; Mo, Xin; An, Yuan; Zhou, Peng (Frontiers in Plant Science, 2022)
Late embryonic development abundant proteins (LEAs) are a large family of proteins commonly existing in plants. LEA_2 is the largest subfamily in the LEA, it plays an important role in plant resistance to abiotic stress. In this study, we have identified and analyzed the MsLEA_ 2 gene family of alfalfa with a complete description of their phylogenetic relationships, chromosome distribution, chromosome collinearity, physical and chemical properties, motif composition, exon-intron structure, cis-elements. We have identified 155 LEA_2 family members in alfalfa. The MsLEA_2 genes are distributed on all 32 chromosomes. Among them, 85 genes were present in the gene clusters, accounting for 54.83%, and chromosome Chr7.3 carries the largest number of MsLEA_2 (19 LEA_2 genes on Chr7.3). Chr7.3 has a unique structure of MsLEA_2 distribution, which reveals a possible special role of Chr7.3 in ensuring the function of MsLEA_2. Transcriptional structure analysis revealed that the number of exons in each gene varies from 1 to 3, and introns varies from 0 to 2. Cis-element analysis identified that the promoter region of MsLEA_2 is rich in ABRE, MBS, LTR, and MeJARE cis-elements, indicating MsLEA_2 has stress resistance potential under abiotic stress. RNA-seq analysis showed that the expression of most MsLEA_2 members was up-regulated under aluminum stress. The results of this study manifested novel insights into phylogenetic relationships and possible functions of alfalfa LEA_ 2 genes. And the findings will helpful for the future functional analysis of the LEA_ 2 proteins.